The Analysis of The Beef Cattle Development Policy by Means of Social Aid Program in Gorontalo Province - Sahara, Laode; Pateda, Sri Yenny (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The aims of the study were to analyze the implementation of the policy, to formulate theÂ alternative decision, and to analyze the priority of decision for the beef cattle development policy bymeans of social aid during six months, June untill November 2015. The population were theinstitutions related to the beef cattle development policy. The samples were the part of the relatedinstitution. The primary data were collected by using interview and questionnaire. The respondentswere the leaders of the examined samples. The secondary data were collected by observation anddocumentation. The data were analyzed by using prescriptive analysis and Analytic HierarchyProcess (AHP) was assistanced with Expert Choise. The result of the study indicates that the values ofthe beef cattle development policy face social problem are 0,755 and the economic problem is0,245. The policy decision priority: 1) Government commitment [0,421], 2) Farmer assistance[0,204], 3) Stakeholder coordination [0,202], and 4) Banking financing [0,173].Key Words: Policy, Beef Cattle, Social Aid